2010
DOI: 10.1111/j.1399-6576.2010.02238.x
|View full text |Cite
|
Sign up to set email alerts
|

Gravity is an important determinant of oxygenation during one‐lung ventilation

Abstract: The role of gravity in the redistribution of pulmonary blood flow during one-lung ventilation (OLV) has recently been questioned. To address this controversial but clinically important issue we used an experimental approach that allowed us to differentiate the effects of gravity from the effects of hypoxic pulmonary vasoconstriction on arterial oxygenation during OLV in patients scheduled for thoracic surgery. MethodsForty patients with chronic obstructive pulmonary disease scheduled for right lung tumour rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 17 publications
(22 reference statements)
1
15
0
1
Order By: Relevance
“… 6 , 7 One-lung ventilation (OLV) aggravates the intrapulmonary shunt and dead space, whereas gravitational effects and hypoxic pulmonary vasoconstriction (HPV) act as protective mechanisms. 8 , 9 However, decreased pulmonary artery compliance and increased pulmonary artery stiffness are reported in early COPD without pulmonary hypertension, 10 , 11 and the HPV responses have been reported to be less efficient in patients with COPD. 12 Furthermore, the treatment strategies for hypoxaemia induced by OLV, such as positive end-expiratory pressure (PEEP) and alveolar recruitment, cannot be applied to COPD patients because of concern about high intrinsic PEEP development.…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 One-lung ventilation (OLV) aggravates the intrapulmonary shunt and dead space, whereas gravitational effects and hypoxic pulmonary vasoconstriction (HPV) act as protective mechanisms. 8 , 9 However, decreased pulmonary artery compliance and increased pulmonary artery stiffness are reported in early COPD without pulmonary hypertension, 10 , 11 and the HPV responses have been reported to be less efficient in patients with COPD. 12 Furthermore, the treatment strategies for hypoxaemia induced by OLV, such as positive end-expiratory pressure (PEEP) and alveolar recruitment, cannot be applied to COPD patients because of concern about high intrinsic PEEP development.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with two-lung ventilation (TLV), an increase in peak airway pressure of ~55% occurs during OLV (34,35). Szegedi et al (36) firstly demonstrated that the effect of gravity on V/Q matching, independent of HPV, resulted in more severe oxidative stress on the operated lung. Misthos et al (37) reported that reactivation of the collapsed lung can activate severe oxidative stress, which was correlated with the time of OLV by reviewing 212 cases between 2001 and 2003 of lung injury caused by re-expansion and reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies and reviews have described the influence of gravity on oxygenation and pulmonary blood flow distribution during OLV. [11][12][13][14] In a recent study, Lee et al 12 assessed the pulmonary venous flow using TEE and demonstrated that the lateral decubitus position itself increased the pulmonary blood flow of the dependent lung via the gravitational effect. The pulmonary blood flow increased 10 minutes after the body position change from supine to a lateral decubitus position.…”
Section: Discussionmentioning
confidence: 99%